Bilateral cystic nephroma with pleuropulmonary blastoma. (18th August 2011) - Bhardwaj, Anand Kumar; Sharma, Prem Dass; Mittal, Amit; Sharma, Akshay
Abstract : Cystic nephroma is a rare benign renal neoplasm that is purely cystic and is lined by an epithelium. Bilateral cystic nephromas are even rarer with only a handful cases reported in the literature. A case of a 2-year-old male child who presented with bilateral renal cystic masses later diagnosed as cystic nephromas is presented here. Ultrasound, CT scan and histopathological investigations aided in arriving at the correct diagnosis. The most concerning feature was the presence of a fluid filled cystic mass in the lungs, most probably a pleuropulmonary blastoma which is a rare malignant neoplasm known to be associated with bilateral cystic nephromas. The most common presenting symptoms of cystic nephroma are painless abdominal mass, abdominal or flank pain and haematuria. These tumours usually follow a benign course and nephrectomy alone is curative. A close surveillance of such patients is recommended because of elevated risk of other tumours.